Estudios sistemáticos en Turnera (Turneraceae). II. Series Annulares, Capitatae, Microphyllae y Papilliferae - Arbo, Maria Mercedes (2000)
Turnera L. includes around 100 American species and two African ones, arranged in nine series. In this paper, the following four series embracing 21 species are revised: Annulares, Capitatae, Microphyllae and Papilliferae. Six new taxa are described: T.hatschbachii, T.hatschbachii var. miniata, T.maracasana, and T.princeps of the series Capitatae, T.asymmetríca of the series Microphyllae, and T.caatingana of the series Papilliferae. The species of these four series share the common features of simple and glandular hairs, generally well-developed floral peduncle, absent pedicel, linear or elliptic prophylls, generally warty or granulate fruit, and a floral tube, appendicular in nature, in that it is the product of the fusion of the lower part of the calyx and corolla, with the staminal filaments adnate only at the base. In the series Annulares, Microphyllae and Papilliferae the leaves and young stems are fragrant, the scent being produced by the glandular hairs, and the floral peduncle is shortly adnate to the petiole. Three series, Annulares, Capitatae and Microphyllae, have leaves with generally well developed stipules and a disjunct geographical distribution. The series Annulares and Capitatae have nectaries and villous or hirsute styles, while Microphyllae and Papilliferae lack nectaries and their styles are glabrous or somewhat pilose. In some species of Microphyllae the staminal filaments are joined at the base, forming an annular structure 0,05-0,50 mm high. The seeds are peculiar in Annulares, being very short, with a central, prominent and slightly concave chalaza. In the series Capitatae, the flowers are gathered in short, capitate inflorescences, the length of the peduncles being variable or sometimes wanting, and the seeds are obovoid, reticulate or striate. The leaves of Microphyllae are small, with the stipules adnate to the foliar base; setiform glandular hairs, similar to those of Piriqueta, are exclusive to Turnera collotricha. The only series in the genus with stipitate glandular hairs is Papilliferae. Keys for the identification of series and species as well as illustrations and distribution maps are provided.